Dead and still grateful: deriving mechanisms of social cohesion from deadhead culture - Smith, Stacy L. (Kansas State University, 2017)
Deadheads (fans of the Grateful Dead) created a durable culture that has lasted for over 50 years despite the death of several band members and the break-up of the band in 1995. What mechanisms account for the rise and persistence of this culture? This empirical question informs a theoretical question: what mechanisms are responsible for social cohesion? Social cohesion has been widely studied in sociology, but because these studies range from sovereign states to interpersonal interaction, the field lacks definitional consensus for the term. Instead of focusing on definitions, therefore, this study instead seeks to contribute to the understanding of underlying mechanisms that are responsible for the development and maintenance of social cohesion. This study employs a mixture of qualitative methods: I conducted seven years of face-to-face and online participant observation, conducted 22 semi-structured, informal face-to-face interviews with 39 interviewees, and collected 86 online, long-form surveys (combined n=125). This study uses both inductive and deductive approaches to analyze material gathered from a mixture of qualitative methods: ethnography, open and closed coding of interviews and surveys, and triangulation to the body of historical work on the Grateful Dead. The mechanisms that emerged from this study suggest that processes related to ritual, religion, and identity, all operating through emotion, are central mechanisms in the longtime cohesion evidenced in the deadhead community. Fan behavior at Grateful Dead shows is reminiscent of Durkheim’s description of tribal behavior in The Elementary Forms of Religious Life, and my research shows that fans create collective effervescence, sacred objects, and feel that they are part of something larger than themselves. Randall Collins builds on Durkheim in his theory of Interaction Ritual Chains, which informs the ways in which deadheads, through engaging collectively in intense rituals, create a long-term sense of community. Finally, I explore the structural symbolic interactionist school of identity theory with Stryker, McCall and Simmons, and Burke. When combined, these theories describe influences on deadhead group composition, explore the complex interaction between the individual and the group, and emphasize the role that emotion plays in that identity-work. Using an inductive approach and Hedström and Swedberg’s (1996) typology of mechanisms, I arrive at a number of mechanisms at work in deadhead cohesion: (1) situational (macro-level) mechanisms include internal and external constraint; (2) individual action (micro-level) mechanisms include self-transcendence, self-reinforcement, and self-talk; and (3) transformational (micro-level to macro-level) mechanisms include group maintenance and disruption. Future work should test these mechanisms using a group that shares characteristics with deadhead culture (such as transience, emergence, boundedness, motivation, and with little official structure) such as the grassroots political movement that emerged after the November 2017 national election, as well as hate groups that have existed for years but have recently become more active. Looking forward, more work is needed on meaning-making and the role of emotions in social cohesion. This work has implications for several sociological disciplines, such as group behavior, social movements, and culture, as well as social cohesion, religion, ritual, and identity theory.
Keywords: Social cohesion; Religion; Ritual; Identity; Grateful Dead; Group behavior